The effect of adsorbent additive on clay based adsorbent to the removal of multidye system - Nor Izzatiey, Mohammad Usolli (2011)

(untitled)
The use of cheap and efficient additives has been studied to find an alternative substitution of expensive additives that is used for the removal of dyes from wastewater. Powdered Activated Carbon (PAC) is one of the most expensive yet effective additives. The main reason doing this research is to find the cheapest and effective adsorbent to treat the waste water. The objective of this experiment is to study the effect of adsorbent additives on clay based adsorbent to the removal of multi-dye system. The scopes are to study the influence of pH towards dye removal performance and to study the effect of multi-dye removal by adding different ratio of additive with clay. Clay is used as the adsorbent and four additives are used to increase the efficiency of dyes removal from wastewater which is Zeolite powder, PAC, Chitosan, and Magnesium Chloride. In the study of determining the effective pH towards dye removal, the mass of clay and additives are set to constant and were added into beaker containing 250ml of dyes solution. The range of pH that used is between 1-14. The results show that Zeolite powder, PAC, and Chitosan are effective at acidic solution which is at pH 5 while Magnesium Chloride is effective at pH 11 which is in basic solution. To study the effect of multi-dye removal with different ratio of additives, the experiments are conducted by adding different amount of additive into a constant amount of clay. The mixture is then repeated on dye removal experiment. From the research, result shows that PAC is the most effective additives compared to others which have high percentage of dyes removal for Methylene Blue at 98.98% and Methyl Orange at 99.19%in acidic solution. The result shows that the best percentage of dye removal occur when the ratio of clay and additives are similar. However, PAC is still proven to be the best additives among all which show the highest percentage removal of Methylene Blue at 99.58% and Methyl Orange at 98.86% %. For the conclusion, PAC is the most effective additive used for the removal of dyes in the solution of 1.0g clay and 1.0g PAC at pH 5 which is in acidic solution. Further research should be done to look for the cheapest alternative for PAC.